An innovative high performance pervious concrete with polyester and epoxy resins. (20th December 2019) - Tabatabaeian, Mojtaba; Khaloo, Alireza; Khaloo, Hooman
Graphical abstract: Highlights: Mechanical properties, permeability, and durability of High Performance Pervious Concrete (HPPC) made by polyester and epoxy resins were studied. ANOVA, Signal to Noise (S/N) ratio, and DBA methods were applied to specify the optimum mixture design. The resin type was the most effective on the mechanical properties and permeability, and the resin content was the most effective on freezing-thawing resistance. Regression models were suggested to specify the values of compressive strength, splitting tensile strength, and flexural strength of HPPCs with resins. Abstract: Pervious concrete (PC) has been detecting application in pavement and concrete structures such as dams, small retaining walls, and etc during the past decades. Also, in recent years, the types of resins have been introduced to apply in concrete owing to the enhancing in mechanical and durability characteristics. However, few studies have investigated the mechanical behavior of high performance pervious concrete (HPPC) incorporated by polyester and epoxy resins as polymeric composites, where ordinary cement material has been completely deleted. The purpose of this investigation is to compare the mechanical properties, permeability, and durability of HPPCs made by polymeric composites (i.e. polyester and epoxy resins) with ordinary pervious concrete (OPC) prepared with Portland cement. The mix designs were provided with three various composite contents (12, 14, and 16% by the weight of aggregates), two types of coarse aggregate (4.75–9.5 mm and 9.5–19 mm), and two different types of resins (orthophtalic polyester resin, and bisphenol A-type epoxy resin). The analysis of variance (ANOVA), signal to noise ratio (S/N), and distance based approach (DBA) method as statistical methods were applied to optimize HPPC mix designs based on the strength, durability, and cost. Mechanical tests, including compression, splitting tensile, and flexural tests, were carried out to investigate mechanical properties of HPPCs. Porosity and permeability tests were used to obtain intuitions into the porosity and void content of HPPCs. Moreover, freezing-thawing resistance test was performed to study the durability of HPPCs. Results show that an increase in the resin content from 12% to 16% caused an enhancement in the mechanical behavior and durability of HPPC specimens. Also, this study indicates that HPPCs have better mechanical properties compared with OPC, and make an excellent alternative to OPCs. Moreover, results disclose that polyester resin has better performance compared with epoxy resin. On the other hand, coarse aggregate size adversely affected the mechanical and durability properties. Eventually, a collection of regression models was presented to estimate the mechanical characteristics HPPCs.